Image Reconstruction Using the sinc Kernel Function - Alaverdyan, Suren B. (Изд-во НАН РА)
This study is devoted to address the challenge of solving ill-posed integral equations for image restoration. The integral equation is widely recognized as an ill-posed problem [1]. Our study demonstrates that utilizing a two- dimensional function as a kernel function in the integral equation leads to stable solutions, by establishing a consistent dependence between the solutions and the input data (images). We were able to obtain solutions for the integral equation without employing a regularization process, which significantly reduces the duration of the calculation process. Աշխատանքում ներկայացվել է պատկերների վերականգնման ինտեգրալ հավասարման լուծումներ գտնելու մեթոդ, որը շրջանցում է ոչ կոռեկտ դրված ինտեգրալ հավասարման ռեգուլյարիզացիայի պրոցեսը: Այս հանգամանքը պայմանավորված է պատկերների վերականգնման ինտեգրալ հավասարման ցրման ֆունկցիայի (կորիզ, kernel) ընտրությամբ: Որպես կորիզ ընտրվել է սահմանափակ երկչափ sinc( x; y) ֆունկցիան: В работе представлен метод нахождения решения интегрального уравнения восстановления изображения, который позволяет обойти процесс регуляризации некорректно заданного интегрального уравнения. Это обстоятельство обусловлено выбором функции ядра интегрального уравнения восстановления изображения. В качестве ядра была выбрана ограниченная двумерная функция sinc( x; y) .
Keywords: Mathematical cybernetics; Computer science